Is adult medulloblastoma merely the counterpart of pediatric medulloblastoma? - Gabriel Chun-Hei Wong; Kay Ka-Wai Li; Manix Fung-Man Poon; Ho-Keung Ng (Glioma, 2020)
Medulloblastoma is one of the most common pediatric malignant brain tumors. Its understanding and treatment have advanced rapidly over the decade, with the identification of four distinct molecular groups. In contrast, adult medulloblastoma is a rare entity that accounts for <1% of adult central nervous system tumors, and is understudied in both its genetic landscape and clinical management. Adult medulloblastomas demonstrate many differences from pediatric medulloblastomas that are relevant to clinicians and biologists. Unlike its pediatric counterpart, adult medulloblastomas are typically located laterally in the cerebellum, are seldom metastatic, and commonly relapse beyond 5 years. The distribution and survival outcomes of molecular groups in adult medulloblastoma differ from those in pediatric medulloblastoma, with the sonic hedgehog-activated group being the predominant and most well-studied group in adults. Adult medulloblastomas also exhibit cytogenetic and mutational characteristics unique to this age group, such as the high frequency of telomerase reverse transcriptase promoter mutations and the paucity of MYC and MYCN amplifications. Clinical trials for adult medulloblastoma need to take into account the clinical and biological differences between adult and pediatric medulloblastomas, for example through the use of smoothened inhibitors in adult SHH medulloblastomas to lower the toxicities resulting from direct adoption of pediatric chemotherapeutic regimens. This review summarizes the clinical characteristics, molecular groups, genetic features, and treatment of adult medulloblastoma, with a focus on its differences from pediatric medulloblastoma.